Revealing Self-Assertion in Dior Fall-Winter 2022/2023 Collection Advertising Websites: A Multimodal Discourse Analysis - Salsa Amalika (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
ABSTRACT A website can be used to determine the message that is tried to be brought by the website producers against the viewers as a professional landing page nowadays. This case applied (Djonov, 2007) theory which discussed the sections of website pages. The research also, conducted a descriptive qualitative method with the aim to reveal the concept of self-assertion depicted in verbal and visual elements of Dior Fall-Winter 2022/2023 fashion websites. The data was collected online by using the documentation technique. Then, the data was analyzed using (O’Halloran, 2008) Systemic Functional Linguistics framework. The results of the findings demonstrate that both verbal and visual elements have become such great collaboration to deliver the concept of self-assertion, in which self-assertion was portrayed as attractiveness, uniqueness, and stylish while at the same time bringing attraction to the body, particular parts of the body, and gender (Id et al., 2020). Additionally, self-assertion is not just becoming the representation of self-image, but it also represent an individual’s social class and social aspirations.